Globalization and Gender Equality - Klaus Gründler; Niklas Potrafke; Ramona Schmid; Jan-Egbert Sturm (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Legal rights continue to differ between women and men, particularly in developing countries. In this paper, we examine whether economic integration can improve gender equality by law. We design a novel instrumental variable strategy based on regional waves of globalization, which serve as strong exogenous predictors of national globalization trends. Our main estimate suggests that an increase of one-third in the globalization index, equivalent to a permanent transition from Indonesia to the United States, is associated with a 12.1% increase in gender equality, measured by the extent to which men and women are treated equally by law. We also find that this effect is almost entirely driven by de facto globalization. Linking globalization to more than 300,000 individuals from about 100 countries, we provide evidence for a microfoundation of the macroeconomic effects.
Keywords: F68; F61; O11; O57; K38; 330; gender equality; globalization; economic integration; culture